Pengembangan E-Magazine Berbasis Multipel Representasi untuk Pembelajaran Kimia di SMA pada Materi Larutan Elektrolit dan Non Elektrolit - Endang Jariati; Elvi Yenti (Journal of Natural Science and Integration, 2020)
This research aims to develop learning media in the form of E-Magazine based on multiple representations for chemistry learning in high school on electrolyte and non-electrolyte solution material. E-Magazine is designed using Adobe Flash CS6 software. The type of research used is research and development or research and development (R&D) with the Borg and Gall research model with stages including research and data collection, planning, product development, small-scale trials and product revisions. Data collection techniques used in the form of observation, interviews and questionnaires. Based on the results of the validation of material experts, it was found that the validity of the E-Magazine based on multiple representations for chemistry learning in high school on the resulting electrolyte and non-electrolyte solution material was included in the very valid category with a validity value of 100% and for the validation of media experts a validity value of 88,46% with very valid category. The results of the practicality test obtained a practicality value of 95% in the very practical category and for student responses to the overall contents of the E-Magazine it was found that 50% of students said it was good and 50% of students said it was very good.Keywords: e-magazine, multiple representation, electrolyte and non-electrolyte solution ABSTRAK. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa E-Magazine berbasis multipel representasi untuk pembelajaran kimia di SMA pada materi larutan elektrolit dan non elektrolit. E-Magazine didesain menggunakan Software Adobe Flas CS6. Jenis penelitian yang digunakan adalah penelitian dan pengembangan atau research and development (R&D) dengan model penelitian Borg dan Gall dengan tahapan meliputi penelitian dan pengumpulan data, perencanaan, pengembangan produk, uji coba skala kecil dan revisi produk. Teknik pengumpulan data yang digunakan berupa observasi, wawancara dan angket. Berdasarkan hasil validasi ahli materi diperoleh bahwa validitas E-Magazine berbasis multipel representasi untuk pembelajaran kimia di SMA pada materi larutan elektrolit dan non elektrolit yang dihasilkan termasuk dalam kategori sangat valid dengan nilai validitas 100% dan untuk validasi dari ahli media diperoleh nilai validitas sebesar 88,46% dengan kategori sangat valid. Hasil uji kepraktisan diperoleh nilai praktikalitas sebesar 95% dengan kategori sangat praktis dan untuk respon siswa terhadap keseluruhan isi       E-Magazine diperoleh bahwa 50% siswa menyatakan bagus dan 50% siswa menyatakan sangat bagus.Kata kunci: e-magazine, multipel representasi, larutan elektrolit dan non elektrolit